2021
DOI: 10.3389/fpsyg.2021.631364
|View full text |Cite
|
Sign up to set email alerts
|

Underload on the Road: Measuring Vigilance Decrements During Partially Automated Driving

Abstract: Partially automated vehicle technology is increasingly common on-road. While this technology can provide safety benefits to drivers, it also introduces new concerns about driver attention. In particular, during partially automated driving (PAD), drivers are expected to stay vigilant so they can readily respond to important events in their environment. However, using partially automated vehicles on the highway places drivers in monotonous situations and requires them to do very little. This can place the driver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 71 publications
2
12
0
Order By: Relevance
“…Respondents in the present study were early adopters with a strong technical or professional background and a high level of technology savviness, which may also explain the low subjective workload. Studies have shown that cognitive underload can be detrimental to drivers' take over performance (McWilliams and Ward, 2021). Hence, it is debatable whether the expected improved ability to take over, as reported by our respondents, is realistic.…”
Section: Workloadmentioning
confidence: 76%
See 1 more Smart Citation
“…Respondents in the present study were early adopters with a strong technical or professional background and a high level of technology savviness, which may also explain the low subjective workload. Studies have shown that cognitive underload can be detrimental to drivers' take over performance (McWilliams and Ward, 2021). Hence, it is debatable whether the expected improved ability to take over, as reported by our respondents, is realistic.…”
Section: Workloadmentioning
confidence: 76%
“…It is assumed that automated cars will improve traffic safety, eliminating human error (Ye and Yamamoto, 2019;Tafidis et al, 2022). These assumptions tend to remain speculative and untested, ignoring the emergence of new types of unintended safety risks, which may offset the expected safety benefits (Casner and Hutchins, 2019;McWilliams and Ward, 2021;Malin et al, 2022;Tafidis et al, 2022). Except for social media content (e.g., anecdotes and YouTube videos) (Reddit, 2022a), little is known about the unintended and intended changes of driver state and (travel) behavior with FSD Beta engaged and how these compare to standard Autopilot.…”
Section: Research Gapsmentioning
confidence: 99%
“…This is concerning because the consequences of missing or failing to respond appropriately to vehicle automation failures can be lethal, as demonstrated by recent automationinvolved collisions (e.g., NHTSA, 2017;NTSB, 2019). The research on driver vigilance in automated vehicles suggests that the risk of such collisions will likely grow as a function of time spent driving with automation engaged (Greenlee et al, 2018(Greenlee et al, , 2019Körber, Cingel, Zimmermann, & Bengler, 2015;Körber, Schneider, & Zimmermann, 2015;Mok et al, 2015;McWilliams & Ward, 2021;Saxby et al, 2008;Saxby et al, 2013). Research has shown that driver vigilance is further hindered as monitoring demands are increased by increasing the frequency or reducing the predictability of roadway events that must be inspected for their potential to induce an automation failure (Greenlee et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For example, completing activities like driving or product assembly under high cognitive load often leads to poorer task performance and a greater risk of collisions or work injuries [2][3][4][5]. Likewise, cognitive underload resulting from, for example, boredom, are associated with performance declines in tasks requiring prolonged attentive engagement [6,7].…”
Section: Introductionmentioning
confidence: 99%